Atypical Thrombotic Thrombocytopenic Purpura Presenting as Stroke. (14th January 2019) - Badugu, Pradeepthi; Idowu, Modupe
Abstract : Here we report a case of atypical thrombotic thrombocytopenic purpura that presented as an ischemic cerebrovascular accident. A 56-year-old man with multiple cardiovascular risk factors presented with sudden left-sided weakness, slurred speech, and left facial droop. He showed mild improvement when he was treated with thrombolytic therapy according to the hospital stroke protocol. Later in the course, he developed thrombocytopenia followed by schistocytes revealed by peripheral blood smear and other lab abnormalities. Thrombotic thrombocytopenic purpura (TTP) was suspected, and he was treated with total plasma exchange that improved his condition significantly. This case shows that TTP can have unusual and atypical presentations either with the first episode or upon relapse, making diagnosis extremely difficult. Because patients may not present the expected clinical findings, it is important to be aware of variant presentations. In the early stages of the disease, platelet aggregation and thrombus formation may not be widespread, and thrombocytopenia and microangiopathic hemolytic anemia may not be clinically evident. Patients can present soon after the onset of symptoms when the typical laboratory abnormalities may not have had ample time to manifest. Although most other similar cases in the literature had a previous typical presentation of the disease before an atypical presentation, our patient's first presentation was atypical. An atypical presentation of disease in a patient with cardiovascular risk factors may therefore be extremely difficult to diagnose. We believe that TTP should be considered for any patient presenting with stroke and thrombocytopenia.